If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6 + 6v) = 36 + -1v (6 * 6 + 6v * 6) = 36 + -1v (36 + 36v) = 36 + -1v Add '-36' to each side of the equation. 36 + -36 + 36v = 36 + -36 + -1v Combine like terms: 36 + -36 = 0 0 + 36v = 36 + -36 + -1v 36v = 36 + -36 + -1v Combine like terms: 36 + -36 = 0 36v = 0 + -1v 36v = -1v Solving 36v = -1v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add 'v' to each side of the equation. 36v + v = -1v + v Combine like terms: 36v + v = 37v 37v = -1v + v Combine like terms: -1v + v = 0 37v = 0 Divide each side by '37'. v = 0 Simplifying v = 0
| (2+3w)-1=-6 | | 6y=5 | | (x+2)(x-2)=1 | | -28=196x | | 80000-2x=x | | -6x+4x=-12 | | 8.69=-1-4.7x-x | | 5(2z-1)-4(2+3)=4(2+1) | | 4x=-1+2(x+1) | | 14-(x+5)=4x-6 | | 8-5x=x-16 | | 2(x+3)-5[4-(x-6)]=x+2 | | 4+9=-8+-13 | | 2x+8y=24 | | 4y-6=-2y-11 | | xsuared=x-6 | | -2(5n+2)=4 | | -2.25=-2.6x+0.16 | | g/10+14=5 | | 3(5a-4)= | | 4(3.14)=w-6(3.14) | | 8+3t=4 | | 4x+2y=250 | | 9.5=3.6n+1+2n | | x=190 | | 5(a+4)-4(a+3)=0 | | -3-x=-15 | | 4=1-n+2 | | 14x-4+12x=1x | | -5x+3x=-2 | | 25x^3-100x^2-x+4=0 | | 5-9x-1=1x+6 |